So Which Body Is It? The Concepts of the Body in Psychotherapy - Klopstech, Angela (Bioenergetic Analysis, 2022)
This paper addresses the issue of how the body is conceptualized in modern psychotherapy and, in consequence, how the conceptualizations inform treatment. The paper also addresses the question to which extent a coherent conceptualization of the body and its place in treatment is necessary (or counterproductive), and possible (or even desirable). The author argues for a multiple body perspective where required centering is provided by a selection process. A clinical illustration is also provided.